Idebenone Orchestrates Anti-Inflammatory and Antioxidant Responses to Alleviate Brain Injury After Intracerebral Hemorrhage in Mice - Chen Chen; Liang Cao; Mengzhou Xue; Ning Zhu (Journal of Integrative Neuroscience)
Background: Intracerebral hemorrhage (ICH) is a critical form of stroke with limited treatment options, with secondary brain injury significantly affecting patient outcomes. This study investigated the neuroprotective benefits of idebenone (IDE) in ICH. Methods: An ICH model was established in mice and the temporal progression of oxidative stress and neuroinflammation was evaluated. IDE was then administered intraperitoneally for 3 consecutive days to evaluate its therapeutic effects. Tissue histology was examined after staining with hematoxylin-eosin and TdT-mediated dUTP nick end labeling (TUNEL), while oxidative stress was assessed by western blotting and measurement of malondialdehyde (MDA) levels and neuroinflammation was examined using immunostaining, western blotting, and enzyme-linked immunosorbent assay (ELISA). Results: Oxidative stress and neuroinflammation peaked at 3 days post-ICH, with elevated levels of nuclear factor erythroid 2-related factor 2 (Nrf2) and significant microglial activation. IDE-treated mice had reduced hematoma volumes and improved neurological outcomes. IDE administration decreased Kelch-like ECH-associated protein 1 (Keap1) expression while increasing Nrf2 and NAD(P)H quinone oxidoreductase 1 (NQO1) levels, leading to reduced oxidative damage (p < 0.01, p < 0.05, and p < 0.05, respectively). Moreover, IDE attenuated microglial activation and neutrophil recruitment (p < 0.01, p < 0.01), reduced the levels of matrix metalloproteinase-9 (MMP-9), interleukin-1β (IL-1β), and tumor necrosis factor-α (TNF-α) levels (p < 0.05, p < 0.05, and p < 0.05, respectively), and increased IL-10 expression (p < 0.01). IDE also preserved the integrity of the blood-brain barrier (BBB) and reduced brain edema. Conclusions: The results demonstrated that IDE exerts neuroprotective effects in ICH through the mitigation of oxidative stress and neuroinflammation during the acute injury phase. IDE may be a viable therapeutic intervention for ICH.